Analysis Of Madrasah Aliyah Students’ Errors On Exponent Materials Given Students’ Mathematical Ability Levels - Rohmah, Silatur; Jannah , Ifatul; Qowiyuddin , Agus (Jurnal Multidisiplin Indonesia, 2023)
Errors in solving math problems are often found in the steps of answering math problems by students. These errors can have an impact on the final results of students' answers. For this reason, researchers conducted research on the mistakes that are often made by students in answering math problems in terms of students' mathematical ability levels. This research used descriptive qualitative research methods. The subjects in this study were class X students at MA Abu Amr Paserpan totaling 29 students. Furthermore, researchers only took 6 students to be interviewed. Data collection in this study was carried out using observation, test questions, interviews, and documentation. The results of this study indicate that the types of errors made by students when answering mathematical problems on the material of operating power numbers (exponents) in class X MA Abu Amr Learning Year 2023/2024 consist of three errors, namely, concept errors of 52.29%, language interpretation errors of 48.85% and technical errors of 56.32%. The level of students' mathematical ability also affects the types of errors experienced by these students.